2013
DOI: 10.1016/j.molbiopara.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Increase of gluthatione S-transferase, carboxyl esterase and carbonyl reductase in Fasciola hepatica recovered from triclabendazole treated sheep

Abstract: Fasciolasis is a zoonotic parasitic disease caused by Fasciola hepatica and its control is mainly based on the use of triclabendazole (TCBZ). Parasite resistance to different anthelmintics is growing worldwide, including the resistance of F. hepatica to TCBZ. In the present work we evaluate "in vivo" the activity of xenobiotic metabolizing enzymes of phase I (carboxyl esterases) and phase II (glutathione S-transferases and carbonyl reductases) recovered of flukes from sheep treated with TCBZ. All three enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…However, the low metabolic fate of this compound, observed even in sheep (Michiels et al, 1987), avoids any "protective" GST activity in susceptible F. hepatica. A similar GST activity increase has been reported previously (Scarcella et al, 2013) in the same adult F.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the low metabolic fate of this compound, observed even in sheep (Michiels et al, 1987), avoids any "protective" GST activity in susceptible F. hepatica. A similar GST activity increase has been reported previously (Scarcella et al, 2013) in the same adult F.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…In fact, GST appears to be one of the major detoxification enzymes in parasitic helminths (Precious and Barrett, 1989). GSTs are essentially involved in the intracellular detoxification of numerous substances, including chemotherapeutic agents, and thus play a major role in the development of drug resistance (Cazenave et al, 1989;Hemingway et al, 2004;Scarcella et al, 2013). GSTs can also serve as non-enzymatic binding proteins involved in intracellular transport (Listowsky et al, 1988) and signalling processes (Cho et al, 2001).…”
Section: Closantelmentioning
confidence: 99%
“…Moreover, human carbonyl reductase 3 is induced during pro-inflammatory stimuli and acts as a sensor of oxidative stress 51 . In the trematode parasite F. hepatica , the causative agent of fasciolosis, two xenobiotic metabolizing enzymes (carbonyl reductase and GST) showed an increased activity after in vivo treatment with the anthelminthic drug triclabendazole, suggesting a detoxifying function for this enzyme 52 . In E. granulosus a high level of carbonyl reductase in PSCs exposed to H 2 O 2 might act to detoxify reactive carbonyl, preventing macromolecules damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that when exposed to triclabendazole (TCBZ), there is a significant increase in the expression of carboxylesterase type B (CestB) in F. hepatica [18]. TCBZ is commonly used as an anthelmintic to treat fascioliasis in animals and humans, and the emergence of TCBZ-resistant strains in F. hepatica is primarily associated with its widespread use [2,7].…”
Section: Introductionmentioning
confidence: 99%